Introduced marine species in Croatian waters (Eastern Adriatic Sea) - PECAREVIC, M.; MIKUS, J.; BRATOS CETINIC, A.; DULCIC, J.; CALIC, M. (Mediterranean Marine Science, 2013)
The Croatian part of the Adriatic Sea covers more than 35% of the total Croatian territory, which means that monitoring changes in marine ecosystems and the conservation of biodiversity are of great importance. Following global changes, Croatia is experiencing increasing problems due to the introduction of new species that include aliens (due to aquaculture activities and shipping) and species from other Mediterranean subregions that are extending their geographic range. This work provides a checklist of introduced species in Croatian waters. A total of 113 species (15 phytoplankton, 16 zooplankton, 16 macroalgae, 44 zoobenthic and 22 fish species) have been recorded in the eastern part of the Adriatic Sea, of which 61 species are alien and 52 introduced, due to climate change.